2010
DOI: 10.4049/jimmunol.0903771
|View full text |Cite
|
Sign up to set email alerts
|

A Steady State of CD4+ T Cell Memory Maturation and Activation Is Established during Primary Subtype C HIV-1 Infection

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 52 publications
0
24
0
1
Order By: Relevance
“…The copy numbers of the synthetic HIV-1 standard were calculated from its quantity and molecular weight. Triplicate reactions were run, and the number of template copies was calculated based on the standard curve (20).…”
Section: Cd11bmentioning
confidence: 99%
“…The copy numbers of the synthetic HIV-1 standard were calculated from its quantity and molecular weight. Triplicate reactions were run, and the number of template copies was calculated based on the standard curve (20).…”
Section: Cd11bmentioning
confidence: 99%
“…51,52,58 In those latter studies, activated CD4 + T cells were compared to nonactivated CD4 + T cells, which presumably contained substantial proportions of naive CD4 + T cells, which contain approximately 10-fold less HIV-1 DNA than memory CD4 + T cells. 45,59 One study defined HLA-DR -CD25 -CD69 -as resting cells, 51 but we have found that this subset contains CD38…”
Section: Hiv-1 Dna In Non-gut-homing Cd4mentioning
confidence: 99%
“…One study reported that HIV-1 gag DNA is elevated in activated peripheral blood memory CD4 ϩ T cells (defined as 38 ϩ , DR ϩ , or Ki67 ϩ cells that also expressed CD45RO) than in other memory CD4 ϩ T cells (31), suggesting that activated cells may be preferentially infected in vivo. Nevertheless, neither the proportion of gag DNA nor the amount of HIV-1 RNA produced by activated memory CD4 ϩ T cells was determined in this study.…”
mentioning
confidence: 99%